STUDYING CONDITIONS AND PROBLEMS FOR DEVELOPING MATHEMATICS LEARNING MODEL OF UNDERGRADUATE STUDENTS IN THAILAND - Puchong Praekhaow; Tweesak Chindanurak; Sureerat Areeraksakul Konglok; Kritsana Sokhuma (IKIP Siliwangi and I-MES, 2021)
This research intends to study the conditions and problems of learning management in Mathematics for undergraduate students. Research problem is that students have low achievement and ability problem-solving in mathematics. The research method used is development through the stages of conducting preliminary studies and quantitative survey research, producing initial designs of integrative learning models. The results of this research were used to develop the mathematics learning model. The research was conducted over a one-year period considering two groups. The first sample was collected from the group with 376 students studying mathematics in the academic year 2020. The second sample was collected from the group with 116 professors of public universities in Thailand. Questionnaires were used as a tool of the research. The data analysis was divided into 2 stages. The first stage was to analyze supporting factors with factor analysis. The second stage was to design the learning management of students and professors with regression analysis. The results have shown that the opinions of students and professors on conditions and problems of learning management can be summarized as follows: (1) The students’ opinions for corrections in the aspects were group learning and teamwork, steps of solving problems, a learning model that is real situations, and the problem-based learning, respectively. (2) The professors’ opinions for corrections in the aspects were student interaction, academic achievement, problem-based learning, and learning management model that is current situations, respectively. (3)The supporting factors for the development of the learning management model that professors and students were consistent in solving problems. It was found that there were three main factors as follows; group learning, problem-based learning, and active learning. The learning management model should be developed by integrating group learning, problem-based learning, and step of mathematical problem-solving to enhance problem-solving ability and mathematics learning achievement.